Influence of root canal dressings and sealers on repair of apical periodontitis after endodontic treatment - Berbert, FLCV; Leonardo, M. R.; Silva, LAB; Tanomaru, M.; Bramante, C. M. (Mosby, Inc, 2002)
Objective. The objective of this study was to evaluate the histopathologic response of periapical tissues after root canal treatment of necrotic dog teeth with chronic apical periodontitis by using 2 calcium hydroxide-based root canal dressings and 2 root canal sealers.Study design. Seventy-eight root canals were instrumented by using 5.25% sodium hypochlorite as the irrigating solution, after which a calcium hydroxide paste (Calen/PMCC or Calasept) was placed for 30 days as a dressing. The root canals were then filled by using cold lateral gutta-percha condensation and an enclodontic sealer (Sealapex or AH Plus). After 360 days, the animals were killed by anesthetic overdose; then, the teeth were histologically prepared, sectioned, and stained with hematoxylin and eosin for optical microscopic analysis of apical and periapical tissue repair.Results. Statistical analysis showed that the poorest histopathologic results were observed in the Calasept/AH Plus group and that the Sealapex sealer overall resulted in better apical repair than the AH Plus sealer. The histopathologic results of Calen/PMCC paste with both AH Plus and Sealapex and Calasept paste with only Sealapex were statistically similar but were different from the results of Calasept with AH Plus.Conclusions. The results of this study in the dog showed differences in apical and periapical tissue repair of teeth with chronic apical periodontitis by using 2 calcium hydroxide root canal dressings and 2 sealers. More research is necessary to determine the best combination of dressings and sealers.